FEMALE DEPRESSION IN GUY DE MAUPASSANT'S "MOONLIGHT" - Anidita, Widya Rahma (JURNAL LITERARY CRITICISM, 2019)
This paper investigates the depression experienced by women found in Guy De Maupassant's story which is sought from the characteristics of a woman who is depressed. It can be seen that Maupassant shows how the character of a woman who is depressed is due to the problems she faces while with her husband. With this short story, it is hoped that women can realize that when they get into trouble we should not save it ourselves so that depression does not occur. This paper analyzes the short story "Moonlight" by Guy De Maupassant (1882). Results from this study revealed that Maupassant wanted to show the side of women who were depressed because of their marriage. Results from this study revealed that Maupassant has shown that women are more prone to depression than men. Women who are depressed will experience physical changes and mood swings easily and women who are depressed are also more sensitive to words that are issued by someone. The depression experienced by a woman can come from anywhere including in a marriage like that experienced by Henriette. In short, this study shows that Maupassant shows how when a woman experiences depression.   Keywords Female depression, Moonlight, Henriette and Maupassant